Ecological public health: the 21st century's big idea? An essay by Tim Lang and Geof Rayner. (21st August 2012) - Lang, Tim; Rayner, Geof
Abstract : Public health thinking requires an overhaul. Tim Lang and Geof Rayner outline five models and traditions, and argue that ecological public health—which integrates the material, biological, social, and cultural aspects of public health—is the way forward for the 21st century